Constructing Adult Zebrafish Einthoven’s Triangle to Define Electrical Heart Axes - Zhao, Yali; Chen, Connie; Yun, Morgan; Issa, Thomas; Lin, Andrew; Nguyen, Thao P. (Frontiers in Physiology, 2021)
Zebrafish is a popular high-throughput vertebrate model to study human cardiac electrophysiology, arrhythmias, and myopathies. One reason for this popularity is the purported striking similarities between zebrafish and human electrocardiograms (ECGs). However, zebrafish electrical heart axes were unknown. It is impossible to define heart axis based on single-lead ECG because determination of an electrical heart axis in the frontal plane requires the use of the hexaxial reference system (or Cabrera system) derived from Einthoven’s triangle. Construction of Einthoven’s triangle requires simultaneous ECG recording from at least two Einthoven bipolar leads. Therefore, we systematically constructed the first zebrafish Einthoven’s triangle by simultaneous bipolar dual-lead ECG recording to determine for the first time the three frontal electrical heart axes using the Cabrera system. Comparing zebrafish with human Einthoven’s triangle reveals that their normal frontal electrical axes were reflections of each other across 0o in the Cabrera system. The responsible mechanisms involve zebrafish vs human cardiac activation propagating in the same direction along the heart horizontal axis but in opposite directions along the heart longitudinal axis. The same observations are true for zebrafish vs human cardiac repolarization. This study marks a technical breakthrough in the first bipolar dual-lead ECG recording in live adult zebrafish to construct for the first time zebrafish Einthoven’s triangle. This first systematic analysis of the actual differences and similarities between normal adult zebrafish and human Einthoven’s triangles unmasked differences and similarities in the underlying cardiac axis mechanisms. Insights of the live adult zebrafish main heart axis and its three frontal electrical heart axes provide critical contextual framework to interpret the clinical relevance of the adult zebrafish heart as model for human cardiac electrophysiology.